Analysis of differential metabolites between ‘Zijuan’ and ‘Yingshuang’ tea flowers based on widely targeted metabolomics combined with high performance liquid chromatography - ZHU Wan; WU Ying; LI Xiaoxiang; ZHANG Longjie; LIANG Yuerong; LU Jianliang; ZHENG Xinqiang (浙江大学学报. 农业与生命科学版, 2023)
To explore the differences in flavor between flowers of ‘Zijuan’ and ‘Yingshuang’ tea varieties, the abundance of non-volatile metabolites in two light fermented tea flowers was tested, and the metabolites identified via widely targeted metabolomic technology based on ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). The evaluation factors were evaluated by tea sensory evaluation methods and the contents of taste components, such as catechins and flavonoids, were detected by high performance liquid chromatography and colorimetric method. The results showed that ‘Zijuan’ tea flowers tasted sweet and fresh, and a little bitter and slightly astringent, while ‘Yingshuang’ tea flowers tasted sweet, slightly bitter and a little astringent. There were 219 kinds of significantly differential metabolites, including phenolic acids (56 kinds), flavonoids (46 kinds), lipids (26 kinds), tannins (19 kinds), amino acids and their derivatives (17 kinds) and others between the two varieties. Furthermore, metabolic pathway annotations revealed that amino acid-related metabolic pathways and flavone and flavonol metabolism pathways were the main differential metabolic pathways between ‘Zijuan’ and ‘Yingshuang’ tea flowers. In addition, the total contents of flavonoids and anthocyanins and the contents of catechins and some alkaloids between ‘Zijuan’ and ‘Yingshuang’ tea flowers were significantly different (P＜0.05), while the differences in the soluble sugar contents were not significant. The above results preliminarily showed that the flavonoids made the taste of tea flowers had a certain degree of bitterness and astringency, while compared with those in ‘Yingshuang’, the increase of contents of some amino acids and their derivatives in ‘Zijuan’ tea flowers was the main reason for its fresh taste.